Integrated systems: 'Environmentally clean' aquaculture - Giménez Casalduero F. (Environmental impact assessment of Mediterranean aquaculture farms, 2001)
The negative impact of aquaculture derives mainly from particulate and dissolved nutrients. Different methods have been tried to minimize the effects of nutrient loading. Integrated aquaculture is a feasible method to reduce the environmental impacts of by-products from fish culture. In this paper a revision is made of different models whose main target is the realisation of integrated mariculture, introducing cultivations of algae, molluscs in a fish farm. The use of seaweeds as biofilters to remove dissolved nitrogen from fish pond effluents has been widely studied. Different approaches to integrate the seaweed biofilters into fish culture for a sustainable mariculture have been described by several authors. Therefore, cultivation of molluscs on fish farms may control nutrient production and ensure better water flows around the fish net.
TECAM Seminar on Environmental Impact Assessment of Mediterranean Aquaculture Farms, 2000/01/17-21, Zaragoza (Spain)